Effect of probiotics on giardiasis. Where are we? - Luciana Laranjo Amorim Ventura; Dirce Ribeiro de Oliveira; Maria Aparecida Gomes; Marcia Regina Fantoni Torres (Universidade de São Paulo, 2018)
ABSTRACT Giardiasis, an intestinal infection caused by Giardia lamblia, was recently included in the 'Neglected Diseases Initiative' by the World Health Organization. Symptomatic patients can develop mild diarrhea up to a severe malabsorption syndrome, and children may show significantly impaired cognitive and physical development. Currently, nitroimidazoles are the main class of antibiotic used to treat giardiasis. Despite the efficacy of these drugs, adverse effects and reported resistance have increased, encouraging studies to identify and develop therapeutic alternatives. In this context, probiotics may represent an attractive option. Probiotics are defined as live microorganisms that, when administered in suitable amounts, confer a health benefit to the host. The use of probiotics in the treatment of parasitosis has been suggested because of its beneficial effects, such as a reduced time of gastrointestinal symptoms and parasite load in animal models and humans. Probiotics have been studied as an alternative treatment for giardiasis. In this review, we evaluated probiotic effectiveness in the treatment and prevention of this disease. Based on the studies examined herein, we conclude that probiotics have a beneficial effect on the modulation of giardiasis.